HUBUNGAN ANTARA DURASI DUDUK DENGAN KEJADIAN NYERI LEHER PADA MAHASISWA KEDOKTERAN UNIVERSITAS SRIWIJAYA SELAMA PEMBELAJARAN DARING: The Relationship Between Sitting Duration and The Incidence of Neck Pain on University of Sriwijaya Medical Students During Online Learning - Arwan Bin Laeto; Budi Santoso; Eka Febri Zulissetiana; Siti Sarahdeaz Fazzaura Putri; Ayla Fenezza Ferizon (Forind Press, 2024)
Neck pain is one of the musculoskeletal disorders reported globally, with a fairly high number of incidences. In Indonesia, the incidence of neck pain reaches 46.5%, with symptoms of pain episodes that increase and recur. Neck pain can be caused by several factors, one of which is sedentary activity, such as the duration of sitting every day. The duration of sitting, which is part of the ergonomic factor, causes the body to maintain stative muscle tension for a long time. This study aims to analyze the relationship between sitting duration and the incidence of neck pain in medical students at Sriwijaya University. The method used is observational analysis with a cross-section approach. The number of samples in the study was 63 medical students, which were taken using a simple random technique. The instruments used in data collection were the sitting duration questionnaire and the Nordic Musculoskseletal Questionnaire (NMQ). The data was analyzed using the Chi-square test with a significance level of p = 0.05. The results showed that the distribution of neck pain incidence in this study was 60.3% and the duration of sitting was high, which was above 8 hours per day, reaching 55.6%. The results of the study also showed that there was a significant relationship between the duration of sitting and the incidence of neck pain in medical students at Sriwijaya University (p = 0.01). So, it can be concluded that sitting static for more than 8 hours per day can cause pain in the neck muscles.